The effect of foreign investment on economic development and income inequality - Margit Bussmann; Indra De Soysa; John R. Oneal (University of Bonn, Center for Development Research (ZEF), 2002)
In this paper, we assess the effect of globalization on the distribution of income within countries, focussing on the influence of foreign direct investment. We analyze data for 72 countries, 1970-90. We incorporate in our tests the Kuznets (1955) curve, measures of the character of political institutions, and various aspects of the economy and society that have been emphasized in recent research. Our results are easy to summarize. Globalization has little effect on income inequality within countries. The ratio of foreign direct investment stock to gross domestic product is unrelated to the distribution of income. Income inequality in developing and developed countries is unaffected by the presence of multinational corporations. Nor are alternative measures of economic openness - the trade-to-GDP ratio and Sachs and Warner's (1995) measure of free trade policy - associated with greater inequality. The share of income received by the poorest 20% of society in particular is not influenced by the economic importance of foreign investment. If foreign investment increases average incomes in developing countries, as we confirm here, and does not affect the distribution of income, it must benefit all segments of society in developing countries.
Keywords: 330; International Development; International Relations/Trade; Direktinvestition; Globalisierung; Wirtschaftswachstum; Einkommensverteilung; Kuznets-Kurve; Schätzung; Welt